(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Throughout history, theatres and cinemas have remained central pillars of cultural life, functioning not only as entertainment venues but also as institutions that mirror societal transformations, collective memory, and artistic evolution. In earlier centuries, theatres served as the primary medium for dramatic interpretation, moral discourse, and communal engagement. With the advent of technological innovation, cinemas emerged as an influential cultural force, reshaping the way narratives are produced, consumed, and preserved. This article provides a comparative exploration of theatres and cinemas—both historically and in the modern era— examining their artistic significance, socio-cultural functions, and their changing roles in an increasingly digitalized world.